Improved access to early diagnosis and complete treatment of malaria in Odisha, India - Pradhan, Sreya (PLoS One, 2019)
BACKGROUND: In 2013, the Comprehensive Case Management Programme (CCMP) was initiated to assess the impact of universal access to diagnosis and treatment and improved surveillance on malaria transmission in different settings in Odisha state, India. METHODS: Pairs of intervention and control sub-districts (blocks), matched on malaria incidence were selected in four districts with different transmission intensities. CCMP activities included training and supervision, ensuring no stock-outs of malaria tests and drugs, analysing verified surveillance data, stratifying areas based on risk factors, and appointing alternative providers to underserved areas. Composite risk scores were calculated for each sub-centre using principal component analysis. Post−pre changes (2013–2015 versus 2011–2012) for annual blood examination rates (ABER) and annual parasite incidence (API) across intervention and control groups were assessed using difference-in-difference (DID) estimates, adjusted for malaria transmission risk. RESULTS: In the intervention sub-centres, the mean increase in ABER was 6.41 tests/sub-centre (95%CI 4.69, 8.14; p<0.01) and in API was 9.2 cases diagnosed/sub-centre (95%CI 5.18, 13.21; p<0.01). The control sub-centres reported lower increases in ABER (2.84 [95%CI 0.35, 5.34]; p<0.05) and API (3.68 [95%CI 0.45, 6.90]; p<0.05). The control-adjusted post–pre changes in API showed that 5.52 more cases (95%CI 0.34, 10.70; p<0.05) were diagnosed, and a 3.6 more cases (95%CI 0.58, 6.56; p<0.05) were tested per sub-centre in the intervention versus control areas. Larger differences in post–pre changes in API between intervention and control sub-centres were registered in the higher transmission-risk areas compared with the lower risk areas. All the changes were statistically significant. CONCLUSIONS: Intensive intervention activities targeted at improved access to malaria diagnosis and treatment produced a substantial increase in blood examination and case notification, especially in inaccessible, hard-to-reach pockets. CCMP provides insights into how to achieve universal coverage of malaria services through a routine, state-run programme.